Left posterior parietal theta burst stimulation affects gestural imitation regardless of semantic content. - Vanbellingen, T; Bertschi, M; Nyffeler, T; Cazzoli, D; Wiest, R; Bassetti, C; Kaelin-Lang, A; Müri, R; Bohlhalter, S (2014)
OBJECTIVE: Neuro-imaging studies have suggested that the ability to imitate meaningless and meaningful gestures may differentially depend on superior (SPL) and inferior (IPL) parietal lobule. Therefore, we hypothesized that imaging-guided neuro-navigated continuous theta burst stimulation (cTBS) over left SPL mainly affects meaningless and over left IPL predominantly meaningful gestures. METHODS: Twelve healthy subjects participated in this study. High resolution structural MRI was used for imaging guided neuro-navigation cTBS. Participants were targeted with one train of cTBS in three experimental sessions: sham stimulation over vertex and real cTBS over left SPL and IPL, respectively. An imitation task, including 24 meaningless and 24 meaningful gestures, was performed 'offline'. RESULTS: cTBS over both left IPL and SPL significantly interfered with gestural imitation. There was no differential effect of SPL and IPL cTBS on gesture type (meaningless versus meaningful). CONCLUSIONS: Our findings confirm that left posterior parietal cortex plays a predominant role in gestural imitation. However, the hypothesis based on the dual route model suggesting a differential role of SPL and IPL in the processing of meaningless and meaningful gestures could not be confirmed. SIGNIFICANCE: Left SPL and IPL play a common role within the posterior-parietal network in gestural imitation regardless of semantic content.